Oscillation of neutral differential equations with distributed deviating arguments - Candan, T.; Karpuz, B.; Öcalan, Ö. (Нелінійні коливання, 2012)
In this article, we study oscillatory nature of all solutions of a class of neutral differential equations with distributed deviating arguments. Some examples are also included to show the applicability of the results. Вивчається коливна природа розв’язкiв класу нейтральних диференцiальних рiвнянь з розподiленими вiдхиленими аргументами. Наведено приклади застосування результатiв.